Influence of Serotonin Transporter SLC6A4 Genotype on the Effect of Psychosocial Stress on Cognitive Performance: An Exploratory Pilot Study. Issue 2 (June 2018) - Beversdorf, David Q.; Carpenter, Allen L.; Alexander, Jessica K.; Jenkins, Neil T.; Tilley, Michael R.; White, Catherine A.; Hillier, Ashleigh J.; Smith, Ryan M.; Gu, Howard H.
Abstract : Background and Objective: Previous research has shown an effect of various psychosocial stressors on unconstrained cognitive flexibility, such as searching through a large set of potential solutions in the lexical-semantic network during verbal problem-solving. Functional magnetic resonance imaging has shown that the presence of the short (S) allele (lacking a 43–base pair repeat) of the promoter region of the gene ( SLC6A4 ) encoding the serotonin transporter (5-HTT) protein is associated with a greater amygdalar response to emotional stimuli and a greater response to stressors. Therefore, we hypothesized that the presence of the S-allele is associated with greater stress-associated impairment in performance on an unconstrained cognitive flexibility task, anagrams. Methods: In this exploratory pilot study, 28 healthy young adults were genotyped for long (L)-allele versus S-allele promoter region polymorphism of the 5-HTT gene, SLC6A4 . Participants solved anagrams during the Trier Social Stress Test, which included public speaking and mental arithmetic stressors. We compared the participants' cognitive response to stress across genotypes. Results: A Gene×Stress interaction effect was observed in this small sample. Comparisons revealed that participants with at least one S-allele performed worse during the Stress condition. Conclusions: Genetic susceptibility to stress conferred by SLC6A4 appeared to modulate unconstrained cognitive flexibility during psychosocial stress in this exploratory sample. If confirmed, this finding may have implications for conditions associated with increased stress response, including performance anxiety and cocaine withdrawal. Future work is needed both to confirm our findings with a larger sample and to explore the mechanisms of this proposed effect.